2006
DOI: 10.1007/s10735-006-9032-y
|View full text |Cite
|
Sign up to set email alerts
|

Importin KPNA2, NBS1, DNA Repair and Tumorigenesis

Abstract: During the past 20 years, the MRE11-RAD50-NBS1 complex has become an increasingly important focus in basic and clinical cancer research. One main conceptual step forward was made with the discovery of NBS1 and the understanding of its critical pathophysiological role in Nijmegen breakage syndrome. Major efforts were carried out to define the role in DNA repair of this complex. Recently, basic research has continuously extended our understanding of the complexity of the NBS1 complex. MRE11-RAD50-NBS1 complex ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 54 publications
(63 reference statements)
4
42
0
Order By: Relevance
“…; refs. 18,20,23,24,26). We initially observed that untreated patients with NSCLC prior to radiotherapy had low numbers of RAD50 foci with a significant rise in RAD50 foci directly in parallel with the induction of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; refs. 18,20,23,24,26). We initially observed that untreated patients with NSCLC prior to radiotherapy had low numbers of RAD50 foci with a significant rise in RAD50 foci directly in parallel with the induction of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because RAD50 foci formation in tissue biopsies has been shown to be positively correlated with survival (18,20,24,26), we assessed its prognostic value in circulating cells (Fig. 6).…”
Section: Pd-l1 and Rad50 In Circulating Cells As Potential Prognosticmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus, NBS1 acts as tumor suppressor involved in DNA DSB repair, maintaining genome stability. In the cytoplasm, however, NBS1 provides an oncogenic role, which promotes tumorigenesis through binding and activation of the phosphatidylinositol 3-kinase/AKT pathway (22).…”
Section: Discussionmentioning
confidence: 99%
“…2 Karyopherin a 2 (KPNA2) belongs to the karyopherin family and has been described to have an oncogenic role through the modulation of the subcellular localization of cargo proteins relevant for cancer. 3 KPNA2 is also suspected to be involved in cellular proliferation, differentiation, cell-matrix adhesion, colony formation and migration. [4][5][6][7] Increased KPNA2 expression levels, as compared with normal tissue, have been described in various malignancies including breast cancer, 8 melanoma, 9 ovarian cancer 10 and astrocytoma.…”
mentioning
confidence: 99%